Corneal Sensitivity After Ocular Surgery. Issue 4 (July 2019) - Lum, Edward; Corbett, Melanie C.; Murphy, Paul J.
Abstract : Abstract: The cornea is densely innervated with free nerve endings to provide a high level of sensitivity to foreign bodies or noxious substances. They also provide trophic support to the tissues of the cornea and facilitate their repair and replacement. Any reduction in the function of the nerve endings through disease, contact lens wear, or surgery may lead to corneal disease, damage, or reduced healing. Assessment of the corneal nerve function can be made by the use of specialized instruments (aesthesiometers) that stimulate the corneal nerves using different modalities—mechanical, chemical, and thermal. Each modality assesses the function of a different cohort of corneal nerve type. Ocular surgery, particularly corneal surgery, can produce significant damage to the corneal innervation. However, for the majority of surgical procedures, corneal sensation eventually returns to preoperative levels, given enough time. The principal exceptions to this are penetrating keratoplasty, epikeratophakia, and cryo-keratomileusis, where sensation rarely returns to normal. For all types of surgery, the pattern of corneal sensation loss and recovery depends on the type, depth, and extent of incision because these influence the number of nerve fibers severed, and on the healing response of the patient.